Monitoring the impact of COVID-19 in Myanmar: Mechanization service providers - July 2020 survey round - Takeshima, Hiroyuki; Win, Myat Thida; Masias, Ian (International Food Policy Research Institute, 2020)
Mechanization service providers in Myanmar were originally interviewed by telephone in May 2020 and again in June 2020 to determine how their businesses were being affected by COVID-19 related restrictions. The results of those surveys were published in Myanmar Strategy Support Program Policy Notes 07 and 12, respectively. To trace the continuing impact of the COVID-19 pandemic on their economic activities, a third phone survey of mechanization service providers was done in early-July 2020. This Note reports on the results of the third survey, as well as some trends since the first and the second surveys.